Asymmetries challenging global biodiversity sciences - Leandro O. Salles; Hussam Zaher; Marcos Tavares; Mario C. C. de Pinna; Rosane G. Collevatti; Krister T. Smith; Diego Pol; Hongyu Yi; Nancy B. Simmons; Christopher J. Tribe; Joaquin Arroyo-Cabrales; Nour-Eddine Jalil; et al. (Systematics and Biodiversity, 2026)

Correction to: The crucial role of strengthened heat transport through Halmahera Sea in eastern Indonesian seas heat buildup during 2020–2022 anomalous climatic events - Faisal Amri; Iwan P. Anwar; Ardian M. Rizal; Rahaden B. Hatmaja; Ahmed Eladawy; Aditya R. Kartadikaria; Takashi Nakamura (Ocean Dynamics, 2025)

The crucial role of strengthened heat transport through Halmahera Sea in eastern Indonesian seas heat buildup during 2020–2022 anomalous climatic events - Faisal Amri; Iwan P. Anwar; Ardian M. Rizal; Rahaden B. Hatmaja; Ahmed Eladawy; Aditya R. Kartadikaria; Takashi Nakamura (Ocean Dynamics, 2025)

Synthesis and assessment of fenugreek carbon quantum dots as novel green scale inhibitor - B. A. Abd-El-Nabey; D. E. Abd-El-Khalek; J. M. Anwar; M. A. Abd-El-Fatah (Nanotechnology for Environmental Engineering, 2024)

Elucidating the role of nitrogen and silicon regimes in rice blast management and yield performance of Mushk Budji variety under field conditions - Zakir Amin; F. A. Mohiddin; Ali Anwar; Asif. B. Shikari; Tauseef A. Bhat; Fehim Jeelani Wani; T. A. Raja; Zahoor Ahmad Baba; Najeebul Rehman Sofi; Shugufta Parveen; Heena Altaf (Australasian Plant Pathology, 2024)

The Influence of Fat Mass and Obesity-Associated (FTO) Gene on the Effect of Physical Activity (PA) on Risk of Obesity: Scoping Review - Hamad I. Alrajhi; Anwar B. Almutairi; Hesham N. Alrowayeh (Journal of Science in Sport and Exercise, 2023)

Pattern and drivers of danaine butterfly migration in Southern India: implications for conservation - P. A. Vinayan; M. A. Yathumon; N. S. Sujin; B. N. Anjan Kumar; P. A. Ajayan; P. K. Muneer; N. M. Vishnu; C. S. Anwar; N. R. Anoop (Journal of Insect Conservation, 2023)

A comprehensive review on water pollution, South Asia Region: Pakistan - Rabeea Noor; Aarish Maqsood; Azhar Baig; Chaitanya B. Pande; Syeda Mishal Zahra; Abu Saad; Mariyam Anwar; Sudhir Kumar Singh (Urban Climate, 2023)

Campylobacter bilis, the second novel Campylobacter species isolated from chickens with Spotty Liver Disease, can cause the disease - Thi Thu Hao Van; Canh Phung; Arif Anwar; Timothy B. Wilson; Peter C. Scott; Robert J. Moore (Veterinary Microbiology, 2023)

Effect of Variation in the Mass Ratio on Vortex-Induced Vibration of a Circular Cylinder in Crossflow Direction at Reynold Number = 104: A Numerical Study Using RANS Model - Muhammad Usman Anwar; Maha M. A. Lashin; Niaz B. Khan; Adnan Munir; Mohammed Jameel; Riaz Muhammad; Kamel Guedri; Ahmed M. Galal (Journal of Marine Science and Engineering, 2022)
This study reports on the numerical analysis of the impact of mass ratio on the Vortex-Induced Vibration (VIV) phenomenon of an elastically rigid cylinder, oscillating freely in a crossflow direction. Reynolds-averaged Navier–Stokes (RANS) equations with (k-ω SST) model were used to analyze the flow behavior, amplitude ratio and vortex shedding patterns. The study was performed at constant Reynold number (Re) = 104 with reduced velocity (Ur) ranging from 2 to 14 and mass ratio (m*) of 2.4 and 11. The mass ratio was defined as the ratio between mass of the vibrating cylinder and mass of the fluid displaced. It was found that increasing the mass ratio from 2.4 to 11 resulted in decrease in amplitude response by 80%, 71% and 31% at initial branch, upper to lower transition region and lower branch, respectively. However, the amplitude in the upper branch decreased only 8% at high mass ratio. The peak amplitude observed in the present study was lower than previous experimental and DES results. However, the RANS k-ω SST well captured the vortex shedding modes of 2S, 2P, P + S, and 2T. In 2S mode, two single pairs of vortices were formed, whereas in 2P mode two pairs were generated in single oscillation. Similarly, P + S meant one pair and one individual vortex; whereas 2T mode meant two triplets of vortices generated in one oscillation. The study concluded that increase in mass ratio results in shortening of the lock-in region and decrease in amplitude response.

Analysis and farmers’ perception of climate change in the Kashmir Valley, India - S. Sheraz Mahdi; B. S. Dhekale; Rukhsana Jan; M. Anwar Bhat; Ashaq Hussain; Intikhab Aalum Jehangir; Najeebul Rehman Sofi; Latief Ahmed; Asif M. Iqbal Qureshi; Aziz Mujtaba Aezum; Shabir A. Bangroo; Owais Ali Wani; et al. (Theoretical and Applied Climatology, 2022)

Synthesis of novel fly ash based geo-polymeric membranes for the treatment of textile waste water - B. Ahmad; M. R. Dilshad; B. Haider; M. M. Anwar; H. Ali; S. M. A. Gilani; H. B. Ahmad; M. Farooq (International Journal of Environmental Science and Technology, 2022)

Climate change and Australia’s primary industries: factors hampering an effective and coordinated response - Rebecca Olive Darbyshire; Stephen B. Johnson; Muhuddin Rajin Anwar; Forough Ataollahi; David Burch; Curtis Champion; Melinda A. Coleman; James Lawson; Sarah E. McDonald; Michelle Miller; Jianhua Mo; Mary Timms; et al. (International Journal of Biometeorology, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Accumulation of Trace Metals in Indigenous Fish Species from the Old Brahmaputra River in Bangladesh and Human Health Risk Implications - Sabikunnahar Shorna; Saika Shawkat; Anwar Hossain; Shamshad B. Quraishi; A. K. M. Atique Ullah; Mohammad Mozammal Hosen; Md. Kamal Hossain; Badhan Saha; Bijoya Paul; Md. Habibullah-Al-Mamun (Biological Trace Element Research, 2021)

Dose-dependent therapeutic effects of topical 1,25 OH-vitamin D3 on corneal wound healing - Sayena Jabbehdari; Ghasem Yazdanpanah; Eric Chen; Neda Afsharkhamseh; Mahmood Ghassemi; Khandaker N. Anwar; Cheryl Fonteh; Ali R. Djalilian; Kai B. Kang (Molecular Biology Reports, 2021)

Principles of bone and tissue banking in Saudi Arabia: 10-year experience report - Imran Ilyas; Anwar M. Al-Rabiah; Thamer S. Alhussainan; Husam A. Alrumaih; Abdulelah B. Fallatah; Shuruq A. Alsakran; Omar A. Al-Mohrej (Cell and Tissue Banking, 2021)

Sleep Disordered Breathing in Hypertrophic Cardiomyopathy - Salma I. Patel; Fadi E. Shamoun; Heidi Esser; Sairam Parthasarathy; Michael J. Ackerman; Jeffrey B. Geske; Steve R. Ommen; William T. Love; Virend K. Somers; Anwar A. Chahal; Johan M. Bos; Stephen S. Cha; et al. (Sleep and Vigilance, 2020)

Genetic Variability and DNA Fingerprinting of Elite Mango Genotypes of India Using Microsatellite Markers - Malathi Surapaneni; Lakshminarayana R. Vemireddy; Begum Hameedunnisa; B. Purushotham Reddy; S. Y. Anwar; E. A. Siddiq (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2019)

Chronic Dysregulation of Cortical and Subcortical Metabolism After Experimental Traumatic Brain Injury - Jennifer L. McGuire; Erica A. K. DePasquale; Miki Watanabe; Fatima Anwar; Laura B. Ngwenya; Gowtham Atluri; Lindsey E. Romick-Rosendale; Robert E. McCullumsmith; Nathan K. Evanson (Molecular Neurobiology, 2019)

Genetic characterization and diversity of circulating influenza A/H1N1pdm09 viruses isolated in Jeddah, Saudi Arabia between 2014 and 2015 - Anwar M. Hashem; Esam I. Azhar; Sarah Shalhoub; Turki S. Abujamel; Norah A. Othman; Abdulwahab B. Al Zahrani; Hanan M. Abdullah; Maha M. Al-Alawi; Anees A. Sindi (Archives of Virology, 2018)

Exogenous Glutathione Modulates Salinity Tolerance of Soybean [Glycine max (L.) Merrill] at Reproductive Stage - Soleh Akram; Md. Nurealam Siddiqui; B. M. Nahid Hussain; Md. Abdullah Al Bari; Mohammad Golam Mostofa; Mohammad Anwar Hossain; Lam-Son Phan Tran (Journal of Plant Growth Regulation, 2017)

Characterisation of Clostridium difficile strains isolated from Groote Schuur Hospital, Cape Town, South Africa - B. Kullin; T. Brock; N. Rajabally; F. Anwar; G. Vedantam; S. Reid; V. Abratt (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

The effects of steady swimming on fish escape performance - Sanam B. Anwar; Kelsey Cathcart; Karin Darakananda; Ashley N. Gaing; Seo Yim Shin; Xena Vronay; Dania N. Wright; David J. Ellerby (Journal of Comparative Physiology A, 2016)

Synthesis of enyne and aryl vinyl sulfoxides: functionalization via Pummerer rearrangement - Frederico B. Souza; Anwar Shamim; Luiz M. Z. Argomedo; Daniel C. Pimenta; Hélio A. Stefani (Molecular Diversity, 2015)

Synthesis of C-glycosyl-bis-1,2,3-triazole derivatives from 3,4,6-tri- $$\varvec{O}$$ O -acetyl-D-glucal - Anwar Shamim; Frederico B. Souza; Gustavo H. G. Trossini; Fernando M. Gatti; Hélio A. Stefani (Molecular Diversity, 2015)

Truncation of the E3 ubiquitin ligase component FBXO31 causes non-syndromic autosomal recessive intellectual disability in a Pakistani family - Asif Mir; Kumudesh Sritharan; Kirti Mittal; Nasim Vasli; Carolina Araujo; Talal Jamil; Muhammad Arshad Rafiq; Zubair Anwar; Anna Mikhailov; Sobiah Rauf; Huda Mahmood; Abdul Shakoor; et al. (Human Genetics, 2014)

Population structure and genetic analysis of different utility types of mango (Mangifera indica L.) germplasm of Andhra Pradesh state of India using microsatellite markers - Malathi Surapaneni; Lakshminarayan R. Vemireddy; Hameedunnisa Begum; B. Purushotham Reddy; C. Neetasri; J. Nagaraju; S. Y. Anwar; E. A. Siddiq (Plant Systematics and Evolution, 2013)

SUMO-1 is Associated with a Subset of Lysosomes in Glial Protein Aggregate Diseases - Mathew B. Wong; Jacob Goodwin; Anwar Norazit; Adrian C. B. Meedeniya; Christiane Richter-Landsberg; Wei Ping Gai; Dean L. Pountney (Neurotoxicity Research, 2013)

Screening of rice genotypes for resistance to the brown planthopper, Nilaparvata lugens Stål - M. P. Ali; Salem S. Alghamdi; M. A. Begum; A. B. M. Anwar Uddin; M. Z. Alam; Dingcheng Huang (Cereal Research Communications, 2012)

Effects of Selenium and Exendin-4 on Glucagon-Like Peptide-1 Receptor, IRS-1, and Raf-1 in the Liver of Diabetic Rats - Ghinwa M. Barakat; Mohamed E. Moustafa; Anwar B. Bikhazi (Biochemical Genetics, 2012)

Fate of coliforms and pathogenic parasite in four full-scale sewage treatment systems in India - Vinay Kumar Tyagi; B. K. Sahoo; Anwar Khursheed; A. A. Kazmi; Z. Ahmad; A. K. Chopra (Environmental Monitoring and Assessment, 2011)

Metal pollution records in core sediments of some Red Sea coastal areas, Kingdom of Saudi Arabia - Nadia B. E. Badr; Anwar A. El-Fiky; Alaa R. Mostafa; Bandr A. Al-Mur (Environmental Monitoring and Assessment, 2009)

Gene structure and mutant alleles of PCDH15: nonsyndromic deafness DFNB23 and type 1 Usher syndrome - Zubair M. Ahmed; Saima Riazuddin; Sandar Aye; Rana A. Ali; Hanka Venselaar; Saima Anwar; Polina P. Belyantseva; Muhammad Qasim; Sheikh Riazuddin; Thomas B. Friedman (Human Genetics, 2008)

Autosomal recessive nonsyndromic deafness locus DFNB63 at chromosome 11q13.2–q13.3 - Shahid Y. Khan; Saima Riazuddin; Muhammad Tariq; Saima Anwar; Muhammad I. Shabbir; S. Amer Riazuddin; Shaheen N. Khan; Tayyab Husnain; Zubair M. Ahmed; Thomas B. Friedman; Sheikh Riazuddin (Human Genetics, 2007)

Binding and distribution of three prototype calcium channel blockers in perfused rat liver - Anwar B. Bikhazi; Khalil M. Bitar; Sawsan I. Kreydiyyeh; Rima S. Saleh; Muna M. El-Kasti; Mohamad Z.M. Ibrahim; Omran R. Abul Khoudoud (Molecular and Cellular Biochemistry, 1997)

Adsorption of concanavalin a on human platelets - Anwar B. Bikhazi; Khalil M. Bitar (Annals of Biomedical Engineering, 1982)